Symposium 7: Diversity and Common Ground in Online Learning Community Research : Symposium Introduction - Harris, Rachel (Proceedings of the International Conference on Networked Learning, 2004)
This symposium will present different perspectives on research in the field of online learning communities. As well as providing an overview of the influence of differing theoretical frameworks on research methodologies, the symposium will highlight key issues that need to be addressed to enable research in this area to move forward. While emphasizing the value of diversity in approaches, theoretical influences and methodologies, the need for some common ground will be explored.